1. \begin{aligned}

\int \frac{6x}{\sqrt{1+x^2}} \ \textrm{d}x =

\end{aligned}

2. \begin{aligned}

\int \frac{x}{1+x^2} \ \textrm{d}x =

\end{aligned}

3. \begin{aligned}

\int \frac{x^2}{1-x^2} \ \textrm{d}x =

\end{aligned}

4. \begin{aligned}

\int \ln (2x+1) \ \textrm{d}x =

\end{aligned}

5. \begin{aligned}

\int -2 \sec^{4} \big( \frac{x}{2} – \pi \big ) \ \textrm{d}x =

\end{aligned}

6. \begin{aligned}

\int 2{x}^{3} \sin (3x-1) \ \textrm{d}x =

\end{aligned}

7. \begin{aligned}

\int (2x+1) \ \sqrt{x-1} \ \textrm{d}x =

\end{aligned}

8. \begin{aligned}

\int -3 \cos 3x \ \sqrt{1 \ – \cos 4x} \ \textrm{d}x =

\end{aligned}

9. \begin{aligned}

\int \Big( \sqrt{2x} \ – \ \frac{1}{\sqrt{2x}} \Big) \ \textrm{d}x =

\end{aligned}

10. \begin{aligned}

\int \frac{2}{4{x}^{2} \ – \ 1} \ \textrm{d}x =

\end{aligned}

11. \begin{aligned}

\int \frac{\textrm{d}x}{ \sqrt{x+2} \ – \ \sqrt{x} } =

\end{aligned}

12. \begin{aligned}

\int \frac{({x}^{3} \ – \ 27)}{(3 \ – \ x)} \ \textrm{d}x =

\end{aligned}

13. \begin{aligned}

\int 5x \ \csc(2{x}^{2}) \ \cot (2{x}^{2}) \ \textrm{d}x =

\end{aligned}

14. \begin{aligned}

\int \frac{{x}^{2}+9x+19}{{x}^{2}+8x+15} \ \textrm{d}x =

\end{aligned}

15. \begin{aligned}

\int \cos 4x \ \cos 3x \ \sin 2x \ \textrm{d}x =

\end{aligned}

16. \begin{aligned}

\int -2 \ln^{2} |x| \ \textrm{d}x =

\end{aligned}

17. \begin{aligned}

\int 2 \ \csc^{3} 2x \ \textrm{d}x =

\end{aligned}

18. \begin{aligned}

\int 2 \ \cos^{4} \frac{1}{2}x \ \sin^{3} \frac{1}{2}x \ \textrm{d}x =

\end{aligned}

19. \begin{aligned}

\int 3 \ \cos^{5} 2x \ \textrm{d}x =

\end{aligned}

20. \begin{aligned}

\int -3 \ \cot^{4} 2x \ \textrm{d}x =

\end{aligned}